Struktur Tata Kelola Perusahaan Dan Pengungkapan Modal Intelektual Perusahaan - Meiliana Meiliana; Kho Lidya Merina (Global Financial Accounting Journal, 2017)
This study aimed to determine the effect of corporate governance structures on the extent of intellectual capital disclosure. Variables used in this study are board size, independent commissioner, audit committee, audit committee meeting, external auditor, firm size, leverage, and profitability. The population of this study was companies listed in the Indonesia Stock Exchange (IDX). Samples of this study were the 46 companies listed on Kompas 100 Index in the period 2009-2013, which selected using purposive sampling method. The data of this study were the annual reports. The data obtained were tested with panel regression. The results of this study indicate independent and control variables simultaneously had significant impact on intellectual capital disclosure. Partially, the results show that the board size, independent commissioner, audit committee, external auditor, firm size, leverage, and profitability had significant impact on intellectual capital disclosure. Other variable such as the audit committee meeting has no significant effect on intellectual capital disclosure.